2010
DOI: 10.1097/pap.0b013e3181d97836
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into Merkel Cell Carcinoma

Abstract: Merkel cell carcinoma (MCC) is a rare aggressive cutaneous malignancy of the elderly and immunocompromised populations. The clinical presentation of MCC is nonspecific, with the majority of cases presenting as localized skin involvement. Histologically and immunophenotypically, MCC is defined by both neuroendocrine and epithelial differentiation. Recently, the Merkel cell polyomavirus has been implicated in the pathogenesis of MCC. In addition, there have been numerous studies evaluating the histologic and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
50
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 54 publications
6
50
0
5
Order By: Relevance
“…Moreover, it has been shown that, for example, JC polyomaviruses preferentially infect stem cells or progenitor cells (reviewed in ref. 25). The finding of Ig and kappa and lambda expression in MCCs on the protein level, as has been described in 2 previous independent cDNA microarray studies on the transcriptional level strongly support our model.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, it has been shown that, for example, JC polyomaviruses preferentially infect stem cells or progenitor cells (reviewed in ref. 25). The finding of Ig and kappa and lambda expression in MCCs on the protein level, as has been described in 2 previous independent cDNA microarray studies on the transcriptional level strongly support our model.…”
Section: Discussionsupporting
confidence: 73%
“…On the basis of MCC mouse models, it has been speculated that the cell of origin of MCC derives from epidermal stem cells or other primitive totipotent stem cells (reviewed in refs. 25,26).…”
Section: Discussionmentioning
confidence: 99%
“…1 The incidence of Merkel cell carcinoma has increased in the last several decades, and the United States has an estimated incidence rate of 0.32 per 100 000 persons per year. 2 Merkel cell carcinoma has a predilection for sun exposed areas, most often occurring in the head and neck region.…”
mentioning
confidence: 99%
“…MCC is extremely unusual before the age of 50 (~5% of the cases) and people at risk include those with fair skin, excessive UV-light exposure and immunosuppressed patients. The median age at presentation is 76 years for women and 74 years for men and there is a slight male predominance [Calder & Smoller, 2010]. The majority of the patients are white (94.9%) and chronically immunosuppressed individuals are 10 to 15 times more likely to develop MCC than age-matched controls.…”
Section: Introductionmentioning
confidence: 99%
“…Whether MCC arises from normal Merkel cells is still controversial [The Rockville MCC group, 2009]. Currently, MCC is thought to originate from a primitive totipotent stem cell with the ability to differentiate along divergent histological phenotypes [Calder & Smoller, 2010]. MCC is a rare but aggressive skin cancer of neuroendocrine origin with propensity for local recurrence and regional lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%